ISOLASI DEKSTRIN DARI PATI SORGUM DENGAN PROSES HIDROLISA PARSIAL MENGGUNAKAN ENZIM α-AMILASE - Hanafi Avika Zadha; Wahyu Raharjo (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Starch is widely used in food industry, Native usage cause some problems related to retrogradiation, syneresys, low stability, and low paste resistance due to pH and temperatures changing. That was the reason why starch modification is done by physical, chemical, and enzymatic treatment. This modification is intended to increase the added value of sorghum flour also fixing the properties and characteristic. The aim of this research are to investigate various variabeles which influence in hydrolysis of dextrin. The isolation of dextrin include in three step, (1) preparation, (2) dextrinization (dextrin formation), and (3) product analysist. Dextrin formation consist of two phase, there are gelatinization and liquefaction phase which is done by mixing in certain time. Control variables in this research include: operation temperatures, string speed, CaCl2 need, and enzyme concentration. Independent variables such as Operation time (60;90;120 minutes), pH and Concentration starch (12; 15; 18; 21; 24 %w/v). Product are then analysed by calculating Dextrose Equivalent (DE), The Yield, Swelling power analysis and % solubility.